Integration principles for complex systems. Issue 6 (28th September 2020) - Grumbach, Joshua Logan; Thomas, Lawrence Dale
Abstract: The integration of complex systems is an important aspect of systems engineering. This paper defines six integration principles to consider when planning and executing system development and integration processes. This paper describes these integration principles and validates them through a historical system survey. The 14 systems studied represent both integration successes and integration failures to show the universal applicability of the principles. The historical system analysis supported the validity of four of the six principles. The validity of one of the remaining principles could not be concluded through the evidence gathered. The validity of the final principle was inconclusive due to a lack of evidence found. Understanding these principles and how to apply them to an integration program will increase the probability of successful integration of future systems.